2017
DOI: 10.1002/jib.397
|View full text |Cite
|
Sign up to set email alerts
|

Pediococcus damnosusstrains isolated from a brewery environment carry thehorAgene

Abstract: Beer is recognized as a safe beverage, owing to its excellent microbiological stability provided by its components, especially iso-α-acids from hop and ethanol which have antimicrobial activity. Despite these unfavourable conditions for bacteria, some lactic acid bacteria (LAB) can cause beer spoilage. Resistance to hop compounds is caused, in part, by the product of genes like horA. Understanding how LAB adapts to hop compounds as well as quick detection of these microorganisms is necessary to ensure high-qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…After 24 h incubation, under iso-α acid stress, the bacteria developed a resistance, thus reducing their sensitivity and consequently the kinetics of their destruction, while under β acids stress they were tolerant. Similarly, a study released by Garcia et al (2016), showed that the Pediococcus bacteria were able to grow and adapt to increasing concentrations of hop compounds in culture media and beer, which shows that it could be considered a potential beer spoiler.…”
Section: Effects Of Simultaneous Cultivation Of Pediococcus Pentosaceus and S Cerevisiae Boulardii In Beer Wort And Selective Mediamentioning
confidence: 92%
“…After 24 h incubation, under iso-α acid stress, the bacteria developed a resistance, thus reducing their sensitivity and consequently the kinetics of their destruction, while under β acids stress they were tolerant. Similarly, a study released by Garcia et al (2016), showed that the Pediococcus bacteria were able to grow and adapt to increasing concentrations of hop compounds in culture media and beer, which shows that it could be considered a potential beer spoiler.…”
Section: Effects Of Simultaneous Cultivation Of Pediococcus Pentosaceus and S Cerevisiae Boulardii In Beer Wort And Selective Mediamentioning
confidence: 92%
“…Similar to Lactobacilllus spp., Pediococcus spp. are commonly considered as beer and manufacturing environmental contaminants, a characteristic that encourages research into the identification of resistance factors mainly acquired through specific plasmids and genes [17,22]. In Lambic-style beers (produced by spontaneous fermentation), P. damnosus is one of the main isolated species and can be easily identified as part of the microbiome of the interior surface of wooden barrels [1], in the air, and on other brewery equipment surfaces [23] mainly due to its high oxidative stress resistance and hop tolerance [4].…”
Section: Lactobacillus Spp and Pediococcus Spp Are Often Identified In Mixed-fermentation Beersmentioning
confidence: 99%